ARTIFICIAL INTELLIGENCE &ITS APPLICATIONS (International Journal of Food and Nutritional Sciences, 2022)
It is the science and engineering of making intelligent machines, especially intelligent computer programs. It is related to the similar task of using computers to understand human intelligence, but AI does not have to confineitse lf to methods that are biologically observable. While no consensual definition of Artificial Intelligence (AI) exists, AI is broadly characterizedas the study of computations that allow for perception, reason and action. Today, the amount of data that is generated, byboth humans and machines, far outpaces humans’ ability to absorb, interpret, and make complex decisions based on that data.Artificial intelligence forms the basis for all computer learning and is the future of all complex decision making. This paper examines features of artificial Intelligence,introduction, definitions of AI, history, applications, growth and achievements